Evaluation of macula and retinal nerve fiber layer thickness in postmenopausal women with hormone replacement therapy - Shariffudin, Nor Syahira (2021)
Introduction Menopause is a state of natural ovarian senescence with accompanying estrogen deficiency. It is associated with various systemic manifestations due to estrogen deficiency including vasomotor, genitourinary, sleep disturbance and others. Besides, menopause is also associated with ocular changes. Declination of estrogen causing impaired ocular blood flow as estrogen have the ability to influence the vascular tone and blood flow in organs and tissues; the impaired ocular blood flow is contributing factor in aetiology and progression of glaucoma and age related macular degeneration (ARMD). Hormone therapy is used as the most effective treatment for menopausal symptoms because it reduces the frequency and discomfort causing by declination of estrogen in the body. In the meantime, it also has the advantages towards eyes structures itself. Objective To evaluate macula and retinal nerve fiber layer thickness in postmenopausal women with and without oral hormone replacement therapy (HRT) and to correlate between duration of oral HRT treatment and macula and RNFL thickness. Methods This is a cross sectional study conducted at Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II between July 2019 until November 2020. A total of 100 menopause women who fulfilled selection criteria were selected using non-probability sampling method. They were divided into two groups: Group 1: postmenopausal women with oral HRT treatment and Group 2: postmenopausal women without HRT treatment. The macula and retinal nerve fiber layer thickness were taken using Hiedelberg Spectralis OCT machine for both groups by blinded trained personnel. The participants came only once during the study period. Statistical analysis was performed using SPSS version 26.0. Results There were no significant mean differences of mean macula thickness between postmenopausal women with and without oral HRT except for superior outer macula (p=0.042) and temporal outer macula (p=0.007). Meanwhile, for RNFL thickness, there were no significant mean differences of mean RNFL thickness between postmenopausal women with and without oral HRT except for total temporal (p=0.044), temporal superior (p=0.002) and temporal inferior (p=0.033). There was no significant correlation between macular thickness and RNFL thickness with duration of oral HRT treatment (all p>0.050). Conclusion HRT usage demonstrated positive structural changes on the macula thickness (specifically on superior outer macula and temporal outer macula) and RNFL thickness (over the temporal, temporal superior and temporal inferior). Hence, the usage of HRT is benefited to the ocular structures of postmenopausal women.